A solvent-induced crystal-facet effect of nickel–cobalt layered double hydroxides for highly efficient overall water splitting. Issue 21 (8th September 2022) - Zan, Lingxing; Zhang, Hongling; Ye, Zhangwen; Wei, Qingbo; Dong, Hongliang; Sun, Shiwen; Weng, Qiang; Bo, Xin; Xia, Huicong; Li, Yibing; Fu, Feng
Abstract : CoNi-LDHs with intensively exposed highly active crystal facets manufactured via a solvent-induced strategy exhibit outstanding synergistic catalytic performance towards both the OER and HER. Abstract : Two-dimensional layered materials have been universally acknowledged to be promising candidates for alternative precious metals in the field of catalysis. The crystal-facet effect is currently rare in the field of electrocatalysis and a deep understanding of the catalytic mechanism of bimetallic highly active crystal facets is critical for fabricating high-performance catalysts, but details are still lacking. Herein, we demonstrated a solvent-induced strategy to manufacture well-defined structured CoNi-layered double hydroxides (LHDs) for highly efficient water electrolysis, and gave a detailed mechanism of catalytic activity towards an enhanced OER. Such considerable improvement in catalytic activity was attributed not only to the synergistic catalytic effect of bimetallic hydroxides, but also to the crystal-facet effect, which is caused by the high density of unsaturated-coordination of surface metal atoms. Consequently, the adsorption energy was enhanced and the activation energy of the target reaction was lowered. These unsaturated coordination surface or edge metal atoms can be easily oxidized to form a great amount of active oxyhydroxides, such as β-NiOOH intermediates. In addition, the adjacent Co sites can also regulate the redox reaction kinetics of Ni(OH)2 /NiOOH and synergistically catalyze the OER.